Volcanic Geoheritage and Geotourism Values of the Siverek Columnar Basalts, Şanlıurfa (SE Türkiye) - Mulayim, Oguz; Koroglu, Fatih; Alkac, Onur (Springer Heidelberg, 2025)
The geoheritage of T & uuml;rkiye consists of several unique elements that have attracted the attention of earth scientists, naturalists, and the public. This study examines the Siverek Columnar Basalts (SCB) & Scedil;anl & imath;urfa, SE T & uuml;rkiye, for their geological and aesthetic value, an asset in the geology of southeast T & uuml;rkiye. The SCB are a remarkable geological wonder that is both distinctive and striking. This potential monumental basalt is not observed anywhere else in SE T & uuml;rkiye. These unique features are exposed in areas of highway construction that are candidates to be geosites. This study aims to characterize the SCB through field investigations, examine petrography, and determine their geoheritage significance and geotourism issues. The region has great potential for geotourism, as indicated by the geoheritage in the vicinity. Unfortunately, urban pressure and visitor movements-particularly to the geosite-comprise risks. As a result, a detailed plan is required for geotourism in the area to grow sustainably.
Keywords: Siverek Columnar Basalt; Volcanic geoheritage; Geotourism; Sustainable development